Tidal breathing flow-volume loops in bronchiolitis in infancy: the effect of albuterol [ISRCTN47364493] - Totapally, Balagangadhar R (BioMed Central, 2002)
OBJECTIVES: To evaluate the effect of nebulized albuterol on tidal breathing flow-volume loops in infants with bronchiolitis due to respiratory syncytial virus. DESIGN: A randomized, double-blind, control study. SETTING: Pediatric unit in a community teaching hospital. PARTICIPANTS: Twenty infants younger than 1 year of age (mean age, 5.8 ± 2.8 months) with a first episode of wheezing due to respiratory syncytial virus bronchiolitis. INTERVENTIONS: Chloral hydrate (50 mg/kg) was administered orally for sedation. One dose each of nebulized albuterol (0.15 mg/kg in 3 ml saline) and saline (3 ml) were given at 6 hour intervals in a random order. MEASUREMENTS: Tidal breathing flow-volume loops were obtained before and after each aerosol treatment with a Neonatal/Pediatric Pulmonary Testing System (Model 2600; Sensor Medics, Anaheim, CA, USA). At the same time, the fraction of tidal volume exhaled at peak tidal expiratory flow (PTEF) to total tidal volume (V(PTEF)/V(E)), and the fraction of exhaled time at PTEF to total expiratory time (t(PTEF)/t(E)) were measured. The PTEF, the tidal expiratory flows at 10%, 25%, and 50% of the remaining tidal volume (TEF10, TEF25, and TEF50), and the wheeze score were also determined. RESULTS: There were no significant changes in V(PTEF)/V(E) and t(PTEF)/t(E) after albuterol or saline treatment. PTEF increased significantly both after albuterol and saline treatments but the difference between the two treatments was not significant (P = 0.6). Both TEF10 and the ratio of the tidal expiratory flow at 25% of the remaining tidal volume to PTEF (25/PT) decreased significantly (P < 0.05) after administration of albuterol. All other investigated variables were not significantly affected by aerosol administration. CONCLUSIONS: Nebulized albuterol in infants with mild bronchiolitis due to respiratory syncytial virus did not improve V(PTEF)/V(E) and t(PTEF)/t(E) but did decrease TEF10 and 25/PT.